(untitled) (Social and Environmental Law Journal, 2025)
This review analyzes, problematizes, and connects the discussions presented by the various authors of the book 1964: Critical Views of the Coup: Democracy and Reforms in Populism, edited by Caio Navarro de Toledo. The debates proposed focus mainly on the economic, political, and social aspects that led Brazil to the military coup that lasted from 1964 to 1985. In addition, the book brings together different perspectives on the dictatorship and on the Brazilian context in the period that followed, and finally includes the account of the editor Ênio Silveira, adding an important testimonial dimension to the collection.